ANALISIS KEPUASAN PENGUNJUNG OBJEK WISATA UMBUL PONGGOK KLATEN DITINJAU DARI KUALITAS PELAYANAN, HARGA, DAN PROMOSI - Tifana Ridho Nursinggih; Apriatni E.P. (Universitas Diponegoro, 2018)
Recreation is that something human need. Peoplehave many choices of tourist attractionsone of which is Umbul Ponggok Klaten. UmbulPonggokKlaten has an underwater garden specialization. The companie give the best innovation to fulfill the needs of its visitors. Visitors have there own choices in choosing which services to use, but visitor’s consideration not only on services products, but others factor like quality of service, price and promotion provided by the company. Umbul ponggok always trying to giving the best quality of services, price, and promotion. Companie are always improving their quality of services, give a special offers of promotions, and quality of price. The strategies provided by companie are given in order to give satisfaction to visitors. Type of this research is descriptive analysis, with population of 100 respondents on Umbul Ponggok Klaten’s visitors. Sampling in this research using purpossive sampling technique. Data were collected through questionnaires. Data analysis method used by Importance performance analysis by using SPSS application. This study concludes that the quality of service, price, and promotion canmade a visitor satisfaction. The quality of service has the lowest performance for visitor satisfaction compared with price performance and promotion performance. Based on this, we suggest that both companie has to improve the quality of service on several dimensions of existing services, and saveral attributes of promotion.. This is to increase visitor satisfaction of Umbul Ponggok Klaten to keep customers.